2013
DOI: 10.3917/rief.033.0149
|View full text |Cite
|
Sign up to set email alerts
|

La paternité en contexte de violence conjugale

Abstract: Cet article présente les résultats d’une étude qualitative menée auprès de vingt-deux pères participant à une thérapie de groupe pour violence conjugale. Cette étude avait pour but de comprendre les expériences paternelles de ces hommes et les éléments qui influencent leur paternité. Dans le cadre des entrevues individuelles semi-dirigées, les pères ont été très éloquents quant aux effets de leur violence sur leur paternité, mais ils ont aussi parlé des divers changements qu’ils ont réalisés, sur le plan de le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…The study by Stover et al (2013) revealed that fathers who committed IPV and who had SUPs were more affected at the mental health level and presented more negative parenting practices. The results of a qualitative study by Bourassa et al (2013) with 22 fathers who were IPV perpetrators showed the importance of examining the parental practices of these fathers, who themselves recognized the harmful nature of certain parenting behaviors and the effects of violence on their children. This study likewise underlines the importance of adopting a dynamic, evolving analysis of parenting in men who consult for their IPV, recognizing that they are in a process of change.…”
Section: Common Situations and Multiple Expressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Stover et al (2013) revealed that fathers who committed IPV and who had SUPs were more affected at the mental health level and presented more negative parenting practices. The results of a qualitative study by Bourassa et al (2013) with 22 fathers who were IPV perpetrators showed the importance of examining the parental practices of these fathers, who themselves recognized the harmful nature of certain parenting behaviors and the effects of violence on their children. This study likewise underlines the importance of adopting a dynamic, evolving analysis of parenting in men who consult for their IPV, recognizing that they are in a process of change.…”
Section: Common Situations and Multiple Expressionsmentioning
confidence: 99%
“…In short, it is well known that childhood victimization remains one of the best predictors of IPV (Ehrensaft et al, 2003;Fritz et al, 2012;Gravel, 2017) and that IPV affects the mothers' and fathers' parenting (Bourassa et al, 2008;Burlaka et al, 2017;de la Sablonnière & Fortin, 2010). The addition of associated issues such as MHP and SUP among families with IPV exacerbates these consequences.…”
Section: Common Situations and Multiple Expressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bien des travaux, dont plusieurs quantitatifs, mettent l'accent sur les comportements inadéquats ou à risque (décrits plus haut) que ces pères adoptent envers leurs enfants et la mère (Bancroft et Silverman, 2002 ;Bancroft et al, 2012 ;Fox et Benson, 2004 ;Harne, 2011 ;Holden et Barker, 2004 ;Holden et Ritchie, 1991 ;Sternberg, 1997). Toutefois, quelques études qualitatives permettent aussi d'avoir accès aux discours et aux désirs de ces pères (Bourassa et al, 2013 ;Peled et Perel, 2008). Celles-ci révèlent l'importance que plusieurs hommes accordent à la paternité ainsi que leur désir d'établir une relation significative avec leurs enfants et de réparer les conséquences de leur violence.…”
Section: Sur Le Plan Scientifiqueunclassified
“…D'autres estiment que la paternité de ces hommes doit faire l'objet d'intervention, puisque ceux-ci ont des contacts réguliers avec leurs enfants, même s'ils sont reconnus coupables d'avoir commis des actes de VC (Deslauriers, 2008 ;Salisbury et al, 2009) ou s'il y a séparation conjugale (Peled et Perel, 2007 ;Scott et al, 2007). À cet égard, certains laissent à penser qu'il y a des hommes, en processus de changement, qui désirent établir une bonne relation avec leur enfant ; ainsi leur paternité devrait être abordée en intervention (Bourassa et al, 2013 ;Perel et Peled, 2008). D'ailleurs, des auteurs croient qu'une intervention sur la paternité peut avoir des effets bénéfiques sur l'enfant et sa relation avec son père (Fleck-Henderson et Areán, 2004 ;Mandel, 2002 ;Neugut et al, 2010 ;Peled et Perel, 2007 ;Stover et al, 2011).…”
Section: Introductionunclassified